Tissue-type Plasminogen Activator (tPA) Modulates the Postsynaptic Response of Cerebral Cortical Neurons to the Presynaptic Release of Glutamate - Jeanneret, Valerie; Wu, Fang; Merino, Paola; Torre, Enrique; Diaz, Ariel; Cheng, Lihong; Yepes, Manuel (Frontiers in Molecular Neuroscience, 2016)
Tissue-type plasminogen activator (tPA) is a serine proteinase released by the presynaptic terminal of cerebral cortical neurons following membrane depolarization (Echeverry et al., 2010). Recent studies indicate that the release of tPA triggers the synaptic vesicle cycle and promotes the exocytosis (Wu et al., 2015) and endocytic retrieval (Yepes et al., 2016) of glutamate-containing synaptic vesicles. Here we used electron microscopy, proteomics, quantitative phosphoproteomics, biochemical analyses with extracts of the postsynaptic density (PSD), and an animal model of cerebral ischemia with mice overexpressing neuronal tPA to study whether the presynaptic release of tPA also has an effect on the postsynaptic terminal. We found that tPA has a bidirectional effect on the composition of the PSD of cerebral cortical neurons that is independent of the generation of plasmin and the presynaptic release of glutamate, but depends on the baseline level of neuronal activity and the extracellular concentrations of calcium (Ca2+). Accordingly, in neurons that are either inactive or incubated with low Ca2+ concentrations tPA induces phosphorylation and accumulation in the PSD of the Ca2+/calmodulin-dependent protein kinase IIα (pCaMKIIα), followed by pCaMKIIα-mediated phosphorylation and synaptic recruitment of GluR1-containing α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors. In contrast, in neurons with previously increased baseline levels of pCaMKIIα in the PSD due to neuronal depolarization in vivo or incubation with high concentrations of either Ca2+ or glutamate in vitro, tPA induces pCaMKIIα and pGluR1 dephosphorylation and their subsequent removal from the PSD. We found that these effects of tPA are mediated by synaptic N-methyl-D-aspartate (NMDA) receptors and cyclin-dependent kinase 5 (Cdk5)-induced phosphorylation of the protein phosphatase 1 (PP1) at T320. Our data indicate that by regulating the pCaMKIIα /PP1 balance in the PSD tPA acts as a homeostatic regulator of the postsynaptic response of cerebral cortical neurons to the presynaptic release of glutamate.